Implementation of the SI-IMUN application to improve basic immunization coverage and maternal knowledge: Penerapan aplikasi SI-IMUN untuk meningkatkan cakupan imunisasi dasar dan pengetahuan ibu - Kustiarini, Ari; Dewi Karuniawathy, Sari; Pathiaturrohmi, Siti; Wahyuningsih, Sri; Asmaningrum, Nurfika; Ardiana, Anisah; Supriadi, Zaroan (KHD Production, 2026)
Basic immunization coverage in Indonesia remains suboptimal, partly due to limited maternal health literacy and inadequate access to reliable health information. This community engagement program aimed to enhance maternal knowledge and improve immunization coverage through the implementation of the SI-IMUN (Maternal and Child Immunization Information System) application. The program adopted a participatory approach by involving mothers and integrated health post cadres through technical training, interactive education using the application, and ongoing assistance for immunization monitoring. Program evaluation was conducted using pre- and post-intervention assessments to measure changes in knowledge and user satisfaction. The results demonstrated a significant improvement in maternal knowledge, with an average increase of 76%. Additionally, 68% of users reported that the application was user-friendly, while 97% of cadres and healthcare workers indicated that SI-IMUN effectively supported health education and facilitated field-based immunization monitoring. In conclusion, the SI-IMUN application represents an effective digital innovation for strengthening community-based health promotion and has strong potential for scalability and replication in other primary healthcare settings.